2010
DOI: 10.14310/horm.2002.1283
|View full text |Cite
|
Sign up to set email alerts
|

Complications and risk factors related to the extent of surgery in thyroidectomy. Results from 2,043 procedures

Abstract: OBJECTIVE: To evaluate the rate of complications and the risk factors in relation to the extent of surgery in patients undergoing thyroidectomy in a tertiary university center. DESIGN: Data were collected retrospectively from 2,043 consecutive patients who underwent thyroid surgery for various thyroid diseases at the University Hospital of Patras, Greece, between January 1996 and December 2007. recurrent laryngeal nerve palsy (rLNP) and hypoparathyroidism were set as the primary end points, while hematoma and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
124
2
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(142 citation statements)
references
References 40 publications
4
124
2
12
Order By: Relevance
“…These findings are supported in several other smaller studies, with reported rates for RLNP in thyroid cancer operations ranging from 2% to 50%. 1,6,7,13,21 Our data confirm increased incidence of temporary and permanent RLNP in cancer versus benign disease surgery. The incidence of permanent and transient RLNP in thyroid cancer surgery was 0.28% and 1.82%, respectively.…”
Section: Cancer Surgerysupporting
confidence: 72%
“…These findings are supported in several other smaller studies, with reported rates for RLNP in thyroid cancer operations ranging from 2% to 50%. 1,6,7,13,21 Our data confirm increased incidence of temporary and permanent RLNP in cancer versus benign disease surgery. The incidence of permanent and transient RLNP in thyroid cancer surgery was 0.28% and 1.82%, respectively.…”
Section: Cancer Surgerysupporting
confidence: 72%
“…Large case series suggest that rates of these complications are: haematoma, 1·2–2·1 per cent1, 2, 3, 4; transient hypoparathyroidism, 6·4–35·2 per cent1, 2, 4, 5, 6; permanent hypoparathyroidism, 0·9–6·3 per cent1, 2, 3, 5, 6; transient RLN injury, 0·36–3·9 per cent1, 2, 3, 4, 5; and permanent RLN injury, 0·7–1·4 per cent1, 2, 3, 5. Short‐term complications increase length of stay in hospital, the number of consultations, diagnostic tests and treatments needed, and overall cost.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory tests including perioperative PTH level, total calcium, ionized calcium, and phosphorus level were evaluated (3,(9)(10)(11)(12)(13)(14)(15)(16). In most of these studies, postoperative serum PTH was recommended as the most powerful predictor for post-thyroidectomy hypocalcemia, with a sensitivity ranging from 64% to 100% and a specificity ranging from 72% to 100%.…”
Section: Discussionmentioning
confidence: 99%